Linfoma Não-Hodgkin: revisão morfológica, clínica, tratamento e evolução. Experiência do Hospital das Clínicas da UFMG no período de 2000 a 2005. - Gianne Donato Costa Veloso (2007)
INTRODUCTION: Non-Hodgkin lymphomas (NHL) are responsible for 4% of all neoplasia in United States. There are few publications about epidemiology and clinical presentation/evolution in Brazil, thus studies about NHL presentation, results and strategies of treatment are justified. OBJETIVES: Describe clinical, and laboratory presentation, treatment and its results in a cohort of patients with NHL follow at Hospital das Clínicas da Universidade Federal de Minas Gerais (HCUFMG). MATERIAL AND METHODS: One hundred and sixty-seven patients older than 16 year-old with a morphological/immunohistochemistry diagnosis of NHL made at Anatomia Patológica Division of the School of Medicine of UFMG andtreated at HC-UFMG from January 2000 to December 2005 were included. Diagnosis of NHL was reviewed and classified according to the World Health Organization proposition. Clinical, laboratorial and morphological features at presentation, treatment, response rate and overall survival were analyzed. RESULTS: There was a predominance of male gender (1.3:1), with a median age of 55.6 years. Eighty-one (48.5%) patients presented B symptoms and performance status in 132 (79.6%) was classified as 0 or 1. B-cell phenotype (77.2%) and diffuse large B cell NHL (37.1%) predominates. Fifty-five per cent of patients presented with an Ann Arbor stage III or IV and at least one extra nodal organ was involved in 69.5% of cases. Anthracyclin-based treatment was the mostfrequent chemotherapy used for aggressive NHL treatment. Complete response (CR) rate for the first treatment was 30.6%, and 25% were refractory. Variables independently associated with a lower CR rate were Ann Arbor stage III or IV (HR=7.14;CI95%=2.13-25), hepatomegaly (HR=7.14;CI95%=1.08-50), and splenomegaly (HR=20;IC95%=2.63-100). Overall survival was 40.7% in 5 years.Survival was significantly better for patients with complete or partial response. A lower probability of survival was associated with a T phenotype (HR=100; CI95%= 14.29->100), performance status higher than 1 (HR=1.75;CI95%=1.09-2.78), hepatomegaly (RR=3.23;CI95%=1.18-9.09) and thrombocytopenia (HR=14.29;CI95%= 3.70-50). A lower probability of survival in patients with aggressive NHL treated with anthracyclins were associated with a T phenotype (HR=7.14; CI95%=2.86-16.67) and an adjusted IPI with more than two risk factors (HR= 3.33; CI95%= 1.45-7.69). CONCLUSIONS: In adult patients with a diagnosis of NHL treated at HC-UFMG, response rate and overall survival were inferior to those reported in the literature although characteristics, stage and treatments were similar. Patients with an Ann Arbor stage III or IV, or with hepatosplenomegaly might have a better outcome if treated with more aggressive chemotherapyregimens since, with the current treatment, chance to achieve a complete response was lower.